Motivation in Reading Among Learners of English as a Second Language - Ali, Zahid; Gopang, Illahi Bux; Qassemi, Farhad; Bughio, Faraz Ali (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The prominent significance of motivation on all skills of language learning is brilliant to all. Despite considerable researches have been done on motivation, there is no sufficient study on the effects of motivation on reading. So far, this study attempts to demonstrate influences of different types of motivation on reading of second language learners. Using a qualitative case study approach, this study examines different aspects of motivation affects on 20 Malaysian girls studying in Master Degree in University of Malaya. The candidates took part in an interview and all questions were explained to them and then they filled up a reconstructed Wigfield questionnaire. The challenge of identifying different types of motivation led to finding out that efficacy and competition in reading plays significant role in reading activities. In sum, the data is presenting the crucial issue that extrinsic and intrinsic motivation empowers each other.